Aves, Emberizidae, Coryphospingus pileatus (Wied, 1821): A new gathered bird species to São Paulo state and evidences of southern geographic expansion in Brazil - Cestari, César [UNESP]; Pacheco, José Fernando (Pensoft Publishers, 2010)
The Pileated Finch Coryphospingus pileatus has an extensive geographic range that encompasses northeast to central, east and part of southeastern regions in Brazil. In southeastern region, Rio de Janeiro and Minas Gerais states were treated as southern limit of the species distribution. In the present note, we firstly documented the species to São Paulo state, extending to southern its old-believed geographic distribution. We argued several records of C. pileatus in Vale do Paraíba region since 40 years ago. We also hypothesized the future geographic expansion of the species in São Paulo state. © 2010 Check List and Authors.